Use Of Digital Media As A Learning Alternative During The Covid-19 Pandemic - Dwi Indah Nursita indah; bunga Melati; Dewi Murtasia; Ega Aisa Dita (JETS: Journal of English Teaching Strategies, 2022)
As an effort to prevent the Covid-19 pandemic, the government issued a policy asking every school to ask its students to study at home. This research aims to describe the use of digital media as an alternative learning during the Covid-19 pandemic. This research uses a qualitative descriptive method carried out with a qualitative approach. The data collection technique used was through in-depth interviews. Data analysis techniques use descriptive analysis techniques. The research results show that media use digital used in the learning process on line At SDN Banjaragung 2 during the Covid-19 pandemic, from grade one to grade six, they predominantly used social media whatsapp by taking advantage of all the features it contains. Learning at SDN Banjaragung 2 also utilizes YouTube media to support material that is sometimes difficult to understand. Meanwhile, specifically for sixth grade students, there is additional digital media used in their learning, namely using mediaZoom Cloud Meetings.MediaZoom Cloud MeetingsThis is only used by sixth grade students, namely twice a week due to limited circumstances and takes up too much quota.